Comparison between magnesium sulphate and esmolol in attenuating haemodynamic responses to laryngoscopy and endotracheal intubation - Norhuzaimah J,; Liu, Chian Yong; Muhammad Maaya,; Ooi Su Min, Joanna Su Min (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
During induction of general anaesthesia, the act of laryngoscopy and tracheal intubation stimulates the sympathetic nervous system resulting in an increase in blood pressure and heart rate which may be harmful especially in elderly patients with pre-existing ischaemic heart disease. Several drugs have therefore been used to obtund this increase including esmolol, nicardipine, magnesium sulphate and lignocaine. This prospective, double blind randomised clinical trial compared the efficacy of magnesium sulphate and esmolol in attenuating haemodynamic responses to laryngoscopy and tracheal intubation. One hundred and twenty six ASA I-II patients scheduled for elective surgery requiring general anaesthesia with tracheal intubation were enrolled and randomised into two groups: Group 1 (n = 67) received MgSO4 40 mg/kg diluted in 100 ml normal saline administered over ten minutes, whereas Group 2 (n = 59) received a bolus of esmolol 1.0 mg/kg diluted to 10 ml. Systolic and diastolic blood pressures and heart rate were recorded every minute for subsequent 10 minutes following laryngoscopy and tracheal intubation. Attenuation of the mean systolic and diastolic blood pressures following laryngoscopy and tracheal intubation was significantly larger in Group 2 compared to Group 1. Patients in Group 2 had significantly better suppression of heart rate response compared to Group 1 during the first four minutes after laryngoscopy and tracheal intubation (p<0.05). Attenuation of the haemodynamic response to laryngoscopy and tracheal intubation by esmolol 1.0 mg/kg was more pronounced compared to MgSO4 40 mg/kg in normotensive patients undergoing general anaesthesia for elective surgery.